100 μas Resolution VLBI Imaging of Anisotropic Interstellar Scattering Toward Pulsar B0834+06 - Brisken, W.; Macquart, Jean-Pierre; Gao, J.; Rickett, B.; Coles, W.; Deller, A.; Tingay, Steven (The American Astronomical Society, 2010)
We have invented a novel technique to measure the radio image of a pulsar scattered by the interstellar plasma with 0.1 mas resolution. We extend the “secondary spectrum” analysis of parabolic arcs by Stinebring et al. (2001) to very long baseline interferometry and, when the scattering is anisotropic, we are able to map the scattered brightness astrometrically with much higher resolution than the diffractive limit of the interferometer. We employ this technique to measure an extremely anisotropic scattered image of the pulsar B0834+06 at 327 MHz. We find that the scattering occurs in a compact region about 420 pc from the Earth. This image has two components, both essentially linear and nearly parallel. The primary feature, which is about 16 AU long and less than 0.5 AU in width, is highly inhomogeneous on spatial scales as small as 0.05 AU. The second feature is much fainter and is displaced from the axis of the primary feature by about 9 AU. We find that the velocity of the scattering plasma is 16±10 km s−1 approximately parallel to the axis of the linear feature. The origin of the observed anisotropy is unclear and we discuss two very different models. It could be, as has been assumed in earlier work, that the turbulence on spatial scales of (∼ 1000 km) is homogeneous but anisotropic. However it may be that the turbulence on these scales is homogeneous and isotropic but the anisotropy is produced by highly elongated (filamentary) inhomogeneities of scale 0.05-16 AU.